Sleep deprivation and burnout syndrome among pre-hospital emergency medical service employees in Slovenia - Vladič, Marko (Obzornik zdravstvene nege, 2021)
Introduction: Sleep deprivation and burnout are common in employees who work in shifts, night shifts, overtime as well as those who work under stressful and unpredictable circumstances. The purpose of the study was to explore the quality of sleep, determine burnout level components and investigate the level of these components and their impact on the quality of sleep among employees in pre-hospital emergency medical services.Methods: A quantitative non-experimental research method was used. Data were collected using a standardized Pittsburgh sleep quality index questionnaire and a standardized Maslach burnout inventory questionnaire. The survey was completed by 204 healthcare professionals. Data were analyzed with univariate and bivariate statistics.Results: The average Pittsburgh Sleep Quality Index score was 4.97, s = 3.23. Poorer quality of sleep is exhibited by female respondents (57.4 %), respondents who are employed in more overloaded pre-hospital emergency service units (52.3 %) and those who work 24 hours or more (67.7 %). Overall, 17.6 % respondents exhibited high emotional exhaustion, 32.8 % exhibited high depersonalization and 9.3 % exhibited low personal accomplishment. A weak correlation was present between sleep quality and emotional exhaustion (r = 0.381, p < 0.01), depersonalization (r = 0.293, p < 0.01) and personal accomplishment (r = 0.368, p < 0.01).Discussion and conclusion: Healthcare professionals represent a vulnerable group that is subject to poor sleep quality and burnout syndrome, therefore, the need for empowering them in terms of proper sleep hygiene and burnout prevention is indicated.
Keywords: burnout; Ekipe prve pomoči; emergency medical services; izgorelost; kakovost; nujna medicinska pomoč; Poklicna izgorelost; pomanjkanje spanja; quality; sleep; sleep deprivation; spanje